2013
DOI: 10.1177/0960327112467043
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine prevents doxorubucine-induced cardiotoxicity in rats

Abstract: This study is designed to observe the effects of N-acetylcysteine (NAC) on doxorubucine-induced cardiac toxicity in rats both histologically and biochemically. Totally 32 rats divided equally into four groups were studied. The first group received only 200 mg/kg NAC intraperitoneal (i.p.) once every 24 h for 5 days (group 1); the second group received 20 mg/kg doxorubucine (DOX) i.p. single dose plus NAC 200 mg/kg i.p. once every 24 h for 5 days (group 2); the third group received DOX 20 mg/kg DOX i.p. single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Significantly increased levels of serum CK, γ-GT, FFA, MDA and ROS were found in groups given VB compared with the NC group. As a reliable indicator of myocardial injury, the serum CK level peaked at 6 hr after the administration of VB, consistent with previous reports [ 27 , 28 ]. The liver toxicity of VB was demonstrated by the presence of significantly elevated γ-GT levels, complemented by pathological evaluation of the liver.…”
Section: Resultssupporting
confidence: 91%
“…Significantly increased levels of serum CK, γ-GT, FFA, MDA and ROS were found in groups given VB compared with the NC group. As a reliable indicator of myocardial injury, the serum CK level peaked at 6 hr after the administration of VB, consistent with previous reports [ 27 , 28 ]. The liver toxicity of VB was demonstrated by the presence of significantly elevated γ-GT levels, complemented by pathological evaluation of the liver.…”
Section: Resultssupporting
confidence: 91%
“…NAC has a strong cardioprotective effect, decreases lipid peroxidation in the heart tissue and prevents free radicals-induced damage to the myocardium by its free radical scavenging effect (Arica et al, 2013;Nagoor Meeran and Mainzen Prince, 2011). On the other hand, Gurbuz et al (2009) reported that, NAC protects against CPinduced genotoxic damage due to their antioxidant, nucleophilic properties and to the ability to act as precursors of glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Group II: rats were treated with NAC (200 mg/kg, i.p.) for 5 consecutive days (Arica et al, 2013). Group III: rats were injected i.p.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results reported here agree with those of previous studies, which showed that DOX produces a prooxidant status in the tissues of rats. [2][3][4][5][6][7][8][9][10][11][12] CAR and related derivatives of histidine are found in high concentrations in cardiac muscle. CAR is considered a multifunctional molecule with antioxidant action and operates as a selective inhibitor of protein glycation and protein-protein cross-linking.…”
Section: Discussionmentioning
confidence: 99%